Do genome size differences within Brachionus asplanchnoidis (Rotifera, Monogononta) cause reproductive barriers among geographic populations? - Riss, Simone (Hydrobiologia, 2017)
Genome size in the rotifer Brachionus asplanchnoidis, which belongs to the B. plicatilis species complex, is greatly enlarged and extremely variable (205–407 Mbp). Such variation raises the question whether large genome size differences among individuals might cause reproductive barriers, which could trigger speciation within this group by restricting gene flow across populations. To test this hypothesis, we used B. asplanchnoidis clones from three geographic populations and conducted assays to quantify reproductive isolation among clones differing in genome size, and we examined the population structure of all three populations using amplified fragment length polymorphisms (AFLPs). AFLPs indicated that these populations were genetically separated, but we also found hints of natural gene flow. Clones from different populations with genome size differences of up to 1.7-fold could interbred successfully in the laboratory and give rise to viable, fertile ‘hybrid’ offspring. Genome sizes of these ‘hybrids’ were intermediate between those of their parents, and fitness in terms of male production, population growth, and egg development time was not negatively affected. Thus, we found no evidence for reproductive isolation or nascent speciation within B. asplanchnoidis. Instead, our results suggest that gene flow within this species can occur despite a remarkably large range of genome sizes.